Do Firms Learn from International Trade? - MacGarvie, Megan (The Review of Economics and Statistics, 2006)
Using patent citations as a proxy for the influence of foreign technology on French firms' patents, this paper finds that the inventions of importers are significantly more likely to be influenced by foreign technology than are the inventions of firms that do not import. Furthermore, importers' citations increase relative to similar firms after they start importing. Exporting, in contrast, is not significantly associated with citations to foreign patents. These results persist after controlling for foreign ownership linkages and joint ventures and alliances, and after correcting for selection bias using propensity-score matching.